THE CONCENTRATION AND SPECIALIZATION OF EUROPEAN FUNDS FOR AGRICULTURE IN THE COUNTRIES OF CENTRAL AND EASTERN EUROPE - Daniel STADOLEANU; Mihaela NECULITA; Adrian BUȚA; Stefan PETREA; Alina MOGODAN; Ira SIMIONOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current European policies for agriculture are characterized by efficiency and economic performance. Their main objective is the stability of the environment. For any European country, European integration represent or must represent stability and economic growth, this two elements being essential to adapt to the current macroeconomic changes. The main objective of this paper is to analyse the evolution of the situation of the countries of Central and Eastern Europe regarding the influence of European funds for agriculture. Being members of the European Union, the countries of Central and Eastern Europe had to adopt the acquis communautaire regarding European agricultural policy and must use EU funds for rural development. The aspect that individualizes this paper is the analysis of regional specialization and concentration of European funds for agriculture using the Herfindahl-Hirschman index. The analysis will be based on data from international institutions.